2005
DOI: 10.1177/0884217505276256
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Mammography Screening of Chinese American Women

Abstract: Effective strategies for promoting breast cancer screening among Chinese American women should address ways to improve information-seeking behaviors and access to health care. Cultural affiliation and beliefs should be considered when counseling Chinese American women regarding breast cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 15 publications
(14 reference statements)
4
42
2
Order By: Relevance
“…Likewise, screening behaviors can be affected by geography, socioeconomic status, and cultural differences (Anothaisintawee et al, 2012). According to an intersectional perspective, ethnic majorities tend to follow the early cancer detection guidelines more closely and have a much easier access to resources than the minorities (Guthrie, 2005;Yu and Wu, 2005;Gomez et al, 2007). Consistent with the prior study, the majority (Chinese) in our study was 2 times more adherent towards going for regular mammography when compared to the Korean Chinese.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, screening behaviors can be affected by geography, socioeconomic status, and cultural differences (Anothaisintawee et al, 2012). According to an intersectional perspective, ethnic majorities tend to follow the early cancer detection guidelines more closely and have a much easier access to resources than the minorities (Guthrie, 2005;Yu and Wu, 2005;Gomez et al, 2007). Consistent with the prior study, the majority (Chinese) in our study was 2 times more adherent towards going for regular mammography when compared to the Korean Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as reported in the study by Wang et al (2009) Chinese women were less interested in going for a mammography because the traditional method of cancer prevention promotes maintaining a balanced diet, using herbs, and exercising as the best approach (Wang et al, 2009). Likewise, diversity in individual and sociocultural environment such as cultural affiliation (Yu and Wu, 2005), lack of health services (Yu and Wu, 2005;Gomez et al, 2007;Gao et al, 2012), low perceived awareness (Yu and Wu, 2005;Gomez et al, 2007;Lee-Lin et al, 2007), or low educational level (Lee-Lin et al, 2007), fatalistic attitude (Charkazi et al, 2013), and low perceived risk of breast cancer (Kim et al, 2011) were found to affect the attendance on screenings. Using the Health Belief Model (HBM), screening practices are one of the health promotion behaviors (Lee-Lin et al, 2008;Kim et al, 2011;Charkazi et al, 2013).…”
Section: Factors Associated With Mammography Adherence Among Married mentioning
confidence: 99%
See 3 more Smart Citations